The practice of responsible journalism in the newscasting format of TV patrol Panay - Bangud, Colleen D.
It is often a battle between public service and public interest that calls on the core standard of responsible journalism. TV Patrol Panay is a tabloid newscast format, a form of television programming that has a strong leaning towards sensationalizing news. This research however, seeks to find a systematic pattern as to whether a tabloid news program, such as TV Patrol Panay does practice responsible journalism, despite the common presumption about tabloid practices. A systematic quantitative content analysis was used to scrutinize the practice of responsible journalism in the tabloid news casting of TV Patrol Panay. In the endeavour to measure the concentration of responsible journalism practice in TV Patrol Panay?s tabloid news casting, a quantitative content analysis was applied in the calculation of the news program?s violations against the Journalist?s Code of Ethics. The same procedure was applied to the calculation of the news program?s tendencies towards tabloid practices. The results were then given perceptual readings, and were qualitatively analysed and discussed. Results reveal that TV Patrol Panay practices responsible journalism despite its tabloid news format. Nonetheless, its news program contains negative aspects of tabloid and follows the descriptive format of tabloid. TV Patrol Panay in tabloid news casting format practices responsible journalism. Its news program contains negative aspects of tabloid and follows the descriptive format of tabloid.